Whole-exome sequencing as a diagnostic tool for ipex syndrome - Anh Linh, Duong; Kim Lien, Nguyen Thi; Van Tung, Nguyen; Van Anh, Nguyen Thi; Phuong Mai, Nguyen Thi; Manh Tien, Ngo; My Hanh, Tran Thi; Huy Hoang, Nguyen (Academia Journal of Biology, 2022)
Immune dysregulation-Polyendocrinopathy-Enteropathy-X-linked (IPEX) syndrome is a life-threatening congenital autoimmune disorder caused by mutations in the forkhead box protein 3 (FOXP3) gene. Typical clinical manifestations of IPEX patients are early onset of intractable diarrhea, type 1 diabetes mellitus, and skin diseases. However, other autoimmune types such as severe food allergies, autoimmune cytopenias, autoimmune respiratory illness, and mesangial glomerulonephritis may complicate IPEX diagnosis. In this study, we report a Vietnamese 1-year-old boy with IPEX syndrome due to a hemizygous missense mutation, c.1190G>A (p.Arg397Gln), in exon 12 of the FOXP3 gene (NM_014009.4). The child had dermatitis, diarrhea, respiratory infections, and splenomegaly. The patient's serum routine test results were expected, except for white blood cells and neutrophils were higher than the normal, while IgA concentration was slightly below the normal range. However, he got no signal of diabetes or failure to thrive. Whole exome sequencing was applied to identify a genetic variant, and variant validation was examined using Sanger sequencing. The patient’s genetic mutation was inherited from his mother, an obligate carrier. His father had a normal genotype. This study is the first report of IPEX syndrome in a Vietnamese patient with a mutation in the FOXP3 gene detected by WES. This study provides further evidence for the role of mutations in the FOXP3 gene in patients with IPEX syndrome and demonstrates the need for genetic counselling and prenatal testing. Our results also show that WES sequencing is an effective tool in diagnosing genetic diseases.